La literatura infantil y su incidencia en el desarrollo del lenguaje oral en los niños y niñas de inicial II del centro de desarrollo integral Punto de Partida de la ciudad de Loja. Período lectivo 2013 - 2014 - Chalco Erreyes, Vanessa Soraya (2015)
This research work entitled "CHILDREN'S LITERATURE AND ITS IMPACT ON THE DEVELOPMENT OF ORAL LANGUAGE IN CHILDREN OF INITIAL II INTEGRAL DEVELOPMENT CENTER" BASELINE "CITY OF LOJA. LECTIVO PERIOD 2013 - 2014 ", has been structured and developed in accordance with the regulations of graduations lifetimes of the National University of Loja. In the present investigation was the General Objective: To establish the incidence of children's literature in the development of Oral Language children initial II Integral Center "Starting Point" Development, the city of Loja, school year 2013 -2014. The methods used are: scientist, hypothetical-deductive, inductive, descriptive, analytic-synthetic, historical and statistical. It was used as techniques and instruments, the survey aimed at teachers, application of test PLON-R, applied to children Initial II. It was evident in the results of this investigation that 100% of the teachers believe that children's literature affects the oral language development of children, extended the same percentage used as a form of children's literature for oral language development stories with pictures and songs, 75% use twisters, 50% jingles and riddles, and 25% fables and other methods; 100% of teachers believe that within child curriculum is important Children's Literature for Oral Language Development. The results obtained by applying the test of PLON-R to the children of the Initial II show that in all areas, (FORM, CONTENT AND USE) 50% of children in the classroom Red 1 present normally in the language development, 44% needs improvement and 6% has missed; while the results of the Initial class II Red 2 35% have normal language development, 53% needs improvement and 12% have a delay. DESCRIPTORS: Children's Literature - Language - expression and oral communication - communication skills - methodological strategy.